Spinal cord infarction during physical exertion due to polycythemia vera and aortoiliac occlusive disease: A case report. Issue 35 (August 2018) - Lin, Wei-Pin; Kuan, Ta-Shen; Lin, Cho-I; Hsu, Lin-Chieh; Lin, Yu-Ching
Abstract: Rationale: Spinal cord infarction is rarely caused by hypercoagulable states. Polycythemia vera (PV) is a myeloproliferative neoplasm that can contribute to thrombotic events due to increased blood viscosity. We report a case of spinal cord infarction due to extensive aortic thrombosis caused by PV. Patient concerns: A 56-year-old man presented with acute paraplegia and urinary retention during heavy physical exertion. Diagnoses: Imaging studies revealed spinal cord infarction at the T9 to T12 levels and aortoiliac occlusive disease. PV was diagnosed during workup for elevated hemoglobin level Interventions: The patient received intravenous hydration and anticoagulation for spinal cord infarction. PV was managed with phlebotomy and hydroxyurea. Courses of inpatient and outpatient rehabilitation programs were also given. Outcomes: The patient became urinary catheter-free 5 months after disease onset, and was able to walk with walker. The American Spinal Injury Association Impairment scale also improved from C at diagnosis to D during last follow-up. Lessons: Etiologic workup is important for patients with spinal cord infarction to direct specific treatment strategies. Physical exertion may act as a trigger for infarction in patients at risk for thrombotic events, and monitoring of neurologic status during and after periods of exercise is warranted. Abstract : Supplemental Digital Content is available in the text